Предмет:
МатематикаАвтор:
аноним{ 5 * х + 9 * х * у = 13;
6 * у - 6 * х = 16;
{ 5 * x + 9 * x * y = 13;
6 * y = 16 + 6 * x;
{ 5 * x + 9 * x * y = 13;
y = (16 + 6 * x)/6;
{ 5 * x + 9 * x * y = 13;
y = 2 * (8 + 3 * x)/(2 * 3);
Числитель и знаменатель в дроби в правой части выражения сокращаем на 2, тогда получим:
{ 5 * x + 9 * x * y = 13;
y = (8 + 3 * x)/3;
{ 5 * x + 9 * x * (8 + 3 * x)/3 = 13;
y = (8 + 3 * x)/3;
{ 5 * x + 3 * x * (8 + 3 * x) = 13;
y = (8 + 3 * x)/3;
{ 9 * x ^ 2 + 24 * x + 5 * x - 13 = 0;
y = (8 + 3 * x)/3;
{ x1 = (- 29 - √1309)/(2 · 9) ≈ - 3.6211;
x2 = (- 29 + √1309)/(2 · 9) ≈ 0.39889;
y = (8 + 3 * x)/3;
{ x1 = (- 29 - √1309)/(2 · 9) ≈ - 3.6211;
x2 = (- 29 + √1309)/(2 · 9) ≈ 0.39889;
y1 = - 0.9544;
y2 = 0.0656.
Автор:
josafatДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть